2022
DOI: 10.1177/19375867211059078
|View full text |Cite
|
Sign up to set email alerts
|

Designing Palliative Care Facilities to Better Support Patient and Family Care: A Staff Perspective

Abstract: Objective: To contribute staff perspectives on the design of palliative care facilities to better align with the philosophy of palliative care, in support of patient, family, and staff well-being. Background: The receipt of palliative care differs from other inpatient experiences owing to its distinct philosophy of care, longer lengths of stay, a greater presence of family members, and more frequent end-of-life events. While research regarding the optimal design of palliative care environments recognizes these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Further, limited family space in some rooms, poor family amenities, limited or nonexistent outdoor access, and a clinical multipurpose room used for family meetings highlight the nurses’ frustration in providing care in their regional hospitals where it seemed palliative, or end-of-life care received little priority and minimal budget allocation. Recent research by McLaughlan et al (2022) reported that nurses felt frustrated and distressed when unable to provide the care they aspired to within environments that did not support the philosophy of palliative care, which was evident in the current study.…”
Section: Discussionmentioning
confidence: 54%
“…Further, limited family space in some rooms, poor family amenities, limited or nonexistent outdoor access, and a clinical multipurpose room used for family meetings highlight the nurses’ frustration in providing care in their regional hospitals where it seemed palliative, or end-of-life care received little priority and minimal budget allocation. Recent research by McLaughlan et al (2022) reported that nurses felt frustrated and distressed when unable to provide the care they aspired to within environments that did not support the philosophy of palliative care, which was evident in the current study.…”
Section: Discussionmentioning
confidence: 54%
“…A hospital’s built environment can impact on a inpatient’s experience and outcomes [ 34 ]. Positive design features for optimal palliative care delivery include privacy and homeliness, access to private spaces, outdoor green spaces and lounge areas [ 35 ]. In particular, private spaces for receiving bad news and that are conducive for reflection are important to palliative patients and families [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Underpinning the delivery of palliative care is the desire to provide patients and families with an inpatient experience that is markedly different to that of general hospital care, reflecting the aims of this medical specialty to improve a patient’s quality of life through the enhancement of physical, psychosocial and spiritual well-being (WHO (World Health Organisation 2020). As such, palliative care staff regard their responsibilities as extending beyond the patient, to the emotional needs of the wider family (McLaughlan et al 2022; Steele and Davies 2015). Ensuring that architectural responses reflected this differentiation emerged as a key priority for clients and their architects.…”
Section: Imparting Care Through the Built Environment: Design Intent ...mentioning
confidence: 99%
“…Yet, given the patient-centred focus of much evidence-based design research, the needs of staff are scarcely discussed within the literature on designing for palliative care. Further, McLaughlan et al (2022) have recently highlighted the risk that, precisely because staff share this patient-centred focus, they are likely to elevate the needs of patients and families above their own resulting in these needs being overlooked within architectural briefing processes. This risk was echoed through the comments of one architect who recounted obtaining critical insight from visiting an existing hospice where the only retreat space available for staff was a storage room:…”
Section: Imparting Care Through the Built Environment: Design Intent ...mentioning
confidence: 99%
See 1 more Smart Citation